Sensitivity of Capnocytophaga species to bactericidal properties of human serum. - Wilson, M E (1985)
Capnocytophaga is a newly described genus of gram-negative bacteria which can cause serious oral and extraoral infections in the susceptible host. In the present study, sensitivity of Capnocytophaga spp. to the bactericidal properties of human serum was investigated. Laboratory strains representative of Capnocytophaga sputigena, C. ochracea, and C. gingivalis and seven oral isolates of Capnocytophaga spp. obtained in primary culture were determined to be sensitive to killing by pooled normal serum. In contrast, little or no killing of Capnocytophaga spp. was observed when these organisms were incubated in the presence of hypogammaglobulinemic serum despite evidence for alternative pathway activation. However, hypogammaglobulinemic serum could be reconstituted to bactericidal activity by the addition of the immunoglobulin M fraction of normal serum. Capnocytophaga spp. failed to activate the classical pathway in hypogammaglobulinemic serum, thus ruling out an antibody-independent mechanism of killing. In contrast, good correlation was observed between serum-mediated killing and antibody-dependent classical pathway consumption. These results indicate that complement in the presence of bactericidal antibody may be an important determinant of host resistance to intra- and extraoral infections caused by Capnocytophaga spp.